Experience and scientific research to substantiate the performance of work in construction - Shatrova, I. E.; Demidova, E. A. (Ways to Improve Construction Efficiency, 2020)
The article provides an analysis of the timeliness of work in construction and experience and research to justify the duration of work in construction. Experience shows that in construction, including housing construction, there is a significant deviation of the actual duration of work from the projected one, which leads to untimely commissioning of residential buildings. Increasing the reliability of justifying the duration of work in construction in conditions of the probabilistic nature of construction production, as experience and research shows, can be carried out on the basis of time reservation to compensate for the negative impact of the micro- and macroenvironment. At the same time, as experience shows, the determination of the duration of construction and installation works, in most cases, is carried out using deterministic methods focused on the use of established standards without taking into account the influence of random factors due to the probabilistic nature of construction production. Other methods, which in one way or another take into account the probabilistic nature of construction production, do not provide an opportunity, when justifying the duration of housing construction work, to determine the optimal level of time reservation required to eliminate the consequences of a negative impact on the progress of work from a large number of random factors. Thus, the development of a scientifically based methodological basis for optimizing the duration of housing construction and a market economy is an urgent problem of scientific and practical importance. Determination of the optimal duration of housing construction work is based on theoretical and methodological systemic principles, which make it possible to determine the optimal level of time reservation and study its dependence on individual organizational and technological factors, taking into account the specifics of construction production and the conditions of a market economy.